Emerging microRNA Therapeutic Approaches for Cystic Fibrosis - Bardin, Pauline; Sonneville, Florence; Corvol, Harriet; Tabary, Olivier (Frontiers in Pharmacology, 2018)
Cystic fibrosis is the most common genetic disease in the Caucasian population, characterized by mutations in the gene encoding the CFTR chloride channel. Although this gene has been known since 1989, the curative therapeutic solutions proposed to patients remain limited. New therapeutic strategies are being explored, such as those targeting microRNAs that participate in the regulation of target messenger RNA expression. This review takes stock of work on the involvement of these microRNAs in cystic fibrosis, particularly in terms of controlling ion channels, inflammation, infection and airway obstruction, and their therapeutic potential.